Sharia Ruling on Financial Derivatives and their Possible Sharia Compliant Alternates - Asghar Kamal; Imran Ullah Khattak (Al-Qanṭara, 2022)
Sharia law is the Islamic moral code and religious law that establishes guidelines for dealing with money as well as other aspects of daily life. Modern finance has seen a rise in the use of financial derivatives like futures and options, although some academics have criticized them for being non-Sharia compatible forms of speculation. Each transaction or contract must, in accordance with Sharia law, involve physical goods or services that are clearly defined and agreed upon by both sides. As a result, Sharia prohibits the use of derivatives that entail speculative transactions or are not based on actual assets. Yet, some academics have proposed substitute financial products that are Sharia legal that could take the place of derivatives. They include Islamic forward contracts, in which two parties mutually agree to buy or sell an asset at a later time, and Islamic swaps, in which cash flows are exchanged in accordance with specified guidelines and conditions. In conclusion, even though some financial derivatives are seen as not complying with Sharia, there may be prospective substitutes that can be used to satisfy the demands of Islamic finance markets. While assessing the Sharia conformity of financial goods, it is crucial to have advice from experienced scholars in the field. Keywords: financial derivatives, Sharia compliant, Musharakah, Salam, Sukuk